Hearing Loss And Health Complaints In Technicians Air Skadron 3 Iswahjudi Airport And Its Association With Aircraft Noise - ristyna choirunisa (Universitas Airlangga, 2019)
Aviation is the most significant part of Indonesian Air Force duty. Air Force's aircraft takes a role not only as Indonesian army agency transportation vehicle but also crucial for Indonesian air territory security protection. However the level of noises resulted from Air Force aviation operation activity such as take off of aircraft reached 130 dBA, so the operation can causes auditory and non auditory adverse effects such as communication, physiological disorder, and psycological disorder. The aim of this study is to analyze factors induced to the hearing loss and analyze the effects of aircraft noises to technician health complaints. This research using case control approach and it was conducted by recruiting subject respondents group randomly of 20 officers includes of 10 technician as study group and 10 non technician as control group. The measurement of aircraft noise level was performed 4 times during 8 hours used Sound Level Meter. The results of aircraft noise measurement in flightline area was exceeding the threshold value of 95,56 dBA. The results of the study shows that aircraft noise significantly associated with to technician hearing loss p-value=0,026 (Spearman correlation test, p<0,05). Other factors that are associated significantly with technician hearing loss include aged p-value=0,023 (Pearson correlation test, p<0,05). Insignificant association is showed for work period with p-value=0,038 (spearman correlation test, p<0,05). In addition, the aircraft noise is associated to health complaint as psychological disorder p-value=0,033 (simple logistic regression test, p-value <0,05). The conclusion of research is that aircraft activities affected hearing loss and technician psychological disorder.